A 6-focus high-concentration photovoltaic-thermal dish system. (October 2017) - Schmitz, Max; Wiik, Nicolay; Ambrosetti, Gianluca; Pedretti, Andrea; Paredes, Stephan; Ruch, Patrick; Michel, Bruno; Steinfeld, Aldo
Graphical abstract: Highlights: A novel 6-focus, high-concentration photovoltaic-thermal system is presented. The design, optical characterization and full-system modeling is shown. The solar dish has a high geometric concentration ratio of 1733× at each of its six receivers. The system can deliver a solar-to-electricity conversion efficiency of 28.5% Low grade heat can be extracted at 89.8 °C at a power of 11.3 kWel /21.5 kWth . Abstract: We present the design, optical characterization and full-system modeling of a novel 6-focus, high-concentration photovoltaic-thermal solar polygeneration system, aiming at an energy-efficient and cost-effective utilization of the solar resource. Essential to this system is a compact, modular solar dish concentrator design optimized for mass-production, structural rigidity, and scalability, with a high geometric concentration ratio of 1733× at each of its six receivers. Every receiver comprises 36 triple-junction CPV cells, interconnected in a unique hybrid parallel-serial scheme that mitigates mismatch losses caused by non-uniform irradiance distributions. Cogeneration is enabled by using high-performance microchannel heat exchangers, allowing the extraction of low grade heat for secondary thermal processes. The tested prototype achieves an average solar radiative flux of 1374 suns on each of the receivers. By optimizing several design parameters, the CPV-thermal system can deliver a solar-to-electricity conversion efficiency of 28.5% in PV-only mode and 26.6% in cogeneration mode while extracting heat at 89.8 °C, and a power of 12.1 kWel and 11.3 kWel /21.5 kWth respectively, matching the performance of state of the art CPV commercial systems, while striving towards a reduction of the investment costs.